Penerapan Metode Anaconda Untuk Mendeteksi Orisinalitas Citra Digital - Erwin Saputra Gultom (BEES: Bulletin of Electrical and Electronics Engineering, 2020)
Image plays a very important role in the form of visual information as one of the multimedia components. The circulation of images in digital form is very easy and fast either through social media or E-mail (Electronic-mail). Digital images are more dynamic and can be easily changed (editable) in terms of shapes, sizes, and objects that are in the digital image. Along with the development of technology and computers, the increase in computer crime has also increased, especially in image manipulation. There are many ways that people use to manipulate images that have a detrimental effect on others. The originality of a digital image is the authenticity of the image in terms of colors, shapes, objects and information without the slightest change from the other party. Nowadays many digital images circulating on the internet have been manipulated and even images have been used for material fraud in the competition, so we need a method that can detect the image is genuine or fake. In this study, the author uses the Anaconda Hash method to detect the originality of digital images, by using this method an image that is still doubtful of its authenticity can be found out that the image is authentic or fake.